Innovative-technological features of teaching children's poetry of the Turkic peoples - Anar Zhapparkulova, Ayimzhan Mukhamedzhanova, Dudarisha Sartbayeva,; Akzia Moldashova, Akylbek Meirbekov, (Opción, 2020)
The article discusses the orientation of the learning process to national values since they are the basis for determining the educational task of innovative learning of Kazakh literature, including the literature of Turkic peoples via comparative qualitative research methods. As a result, the use of new teaching technologies aimed at personal development has a positive effect on teaching high school literature. In conclusion, innovative educational technologies aimed at the personal development of the child are concerned with the development of creativity and activity of the children.